Effects of “Grain for Green” program on soil hydraulic properties: A meta-analysis - Jiao Yang; Huan Ma; Rongfei Zhang; Wei Ji (Geoderma)
Soil hydrologic functions are important for landscapes where soil water loss is significant. The largest ecological restoration engineering project, namely the “Grain for Green” program (GGP), has being implemented since 1999 in China. However, the general patterns of the effects of GGP on soil hydraulic properties under different conditions remain unclear. Aiming to understand the influence of soil hydrologic functions by GGP, a literature review and subsequent meta-analysis were conducted based on the evaluated literature data. The results revealed that GGP significantly increased soil saturated hydraulic conductivity (Ks) by 33.51 %, 23.53 %, and 22.58 % in the surface (0–20 cm), subsurface (20–40 cm) and deep soil layer (>40 cm), respectively. The soil Ks increased over time since GGP implementation. The response changes of Ks showed significant difference among different plantation types, the conversion of cropland to orchards may lead to soil Ks decrease. And the natural restoration approach of grass may lead to greater increase in Ks than artificial restoration approach. In addition, the GLM (General Linear Model) model explained about 97.22 % of the total variables. Among the input variables, soil organic matter content (SOM) explained the largest proportion (39.55 %), followed by plantation type (36.97 %), bulk density (BD) (17.77 %), sand content (2.19 %) and it can be implied that the GGP plays an important positive role in soil hydraulic properties probably because soil organic matter content increased in GGP. This study suggests the GGP implementation caused soil hydrologic functions improving, and provide useful knowledge for ecological restoration practices and management.